27. KNOWLEDGE AND PRACTICES REGARDING HPV AND HPV VACCINATION FOR CERVICAL CANCER PREVENTION AMONG WOMEN VISITING HANOI MEDICAL UNIVERSITY HOSPITAL IN 2024. (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the knowledge and practices regarding HPV vaccination and identify factors associated with knowledge about HPV vaccination for cervical cancer prevention among women visiting Hanoi Medical University Hospital in 2024. .Subjects and Methods: A cross-sectional study was conducted on 378 women aged 18 to 55 who visited the Obstetrics and Gynecology clinics at Hanoi Medical University Hospital.Results: A total of 81.7% of participants had relatively good awareness of HPV and the HPV vaccine. However, misconceptions remained prevalent, especially regarding the self-clearance ability of HPV, with 96.8% misunderstanding this aspect. The HPV vaccination rate was low, at only 24.6%. Factors such as age, educational level, occupation, income, and access to information were significantly associated with knowledge about HPV and HPV vaccination.Conclusion: Knowledge about HPV and vaccination practices among women at Hanoi Medical University Hospital is limited, with low vaccination rates. Strengthening health communication and education programs is critical to improving awareness and promoting HPV vaccination in the community.
Keywords: Cervical cancer; knowledge; practices; HPV; HPV vaccine